Methane pyrolysis in a molten gallium bubble column reactor for sustainable hydrogen production: Proof of concept & techno-economic assessment. (27th January 2021) - Leal Pérez, Brandon José; Medrano Jiménez, José Antonio; Bhardwaj, Rajat; Goetheer, Earl; van Sint Annaland, Martin; Gallucci, Fausto
Abstract: Nowadays, nearly 50% of the hydrogen produced worldwide comes from Steam Methane Reforming (SMR) at an environmental burden of 10.5 tCO2, eq /tH2, accelerating the consequences of global warming. One way to produce clean hydrogen is via methane pyrolysis using melts of metals and salts. Compared to SMR, significant less CO2 is produced due to conversion of methane into hydrogen and carbon, making this route more sustainable to generate hydrogen. Hydrogen is produced with high purity, and solid carbon is segregated and deposited on the molten bath. Carbon may be sold as valuable co-product, making industrial scale promising. In this work, methane pyrolysis was performed in a quartz bubble column using molten gallium as heat transfer agent and catalyst. A maximum conversion of 91% was achieved at 1119 °C and ambient pressure, with a residence time of the bubbles in the liquid of 0.5 s. Based on in-depth analysis of the carbon, it can be characterized as carbon black. Techno-economic and sensitivity analyses of the industrial concept were done for different scenarios. The results showed that, if co-product carbon is saleable and a CO2 tax of 50 euro per tonne is imposed to the processes, the molten metal technology can be competitive with SMR. Highlights: Methane pyrolysis has been carried out in molten metal bubble columns. A techno economic analysis has been carried out. Clean hydrogen is produced at a cost comparable to the one without CO2 capture. The economics depend on the quality of carbon formed and type of process integration.